Genetic Diversity and Selection at the Plasmodium vivax Apical Membrane Antigen-1 (PvAMA-1) Locus in a Sri Lankan Population - Gunasekera, Anusha M.; Wickramarachchi, Thilan; Neafsey, Daniel E.; Ganguli, Ishani; Perera, Lakshman; Premaratne, Prasad H.; Hartl, Daniel; Handunnetti, Shiroma M.; Udagama-Randeniya, Preethi V.; Wirth, Dyann F. (Molecular Biology and Evolution, 2007)
Plasmodium vivax apical membrane antigen 1 (PvAMA-1) is an important malaria vaccine candidate. We present the first comprehensive analysis of nucleotide diversity across the entire PvAMA-1 gene using a single population sample from Sri Lanka. In contrast to what has been observed at the AMA-1 locus of Plasmodium falciparum, the signature of diversifying selection is seen most strongly in Domain II of PvAMA-1, indicating that the different domains in each species may be subject to varying selective pressures and functional constraints. We also find that recombination plays an important role in generating haplotype diversity at this locus, even in a region of low endemicity such as Sri Lanka. Mapping of diversity and recombination hotspots onto a 3-dimensional structural model of the protein indicates that one surface of the molecule may be particularly likely to bear epitopes for antibody recognition. Regions of this surface that show constrained variability may prove to be promising vaccine targets.
Keywords: Selection; Plasmodium vivax; genetic diversity; recombination